The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/aqc.2339
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation of the bocachico Prochilodus magdalenae (Characiformes, Prochilodontidae) in the Magdalena River Basin, Colombia

Abstract: The bocachico Prochilodus magdalenae is a freshwater migratory species of great importance for conservation in Colombia. The populations of this fish have been seriously threatened in the last decade, and there is limited knowledge of its genetic conditions.In order to evaluate the genetic structure of P. magdalenae in the Magdalena River basin and some tributaries, the mitochondrial DNA control region was analysed in samples selected from 20 sites.In total, 189 polymorphic sites were detected on a sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
0
14
2
2
Order By: Relevance
“…The present study demonstrates that P. magdalenae has a high genetic diversity, He = 0.877, compared to that observed for other species of the genus (Santacruz, 2003; Hatanaka et al , 2006; Galzerani, 2007; Carvalho-Costa et al , 2008; Silva, 2011; Rueda et al , 2011) and to other commercially important species that have the same reproductive pattern and migrate long distances (Sanches, 2007; Batista, 2010; Dantas, 2010) (Table 4). Likewise, the microsatellite genetic diversity was slightly lower than that reported by Aguirre et al (2013) for mitochondrial DNA (mtDNA control region) in P. magdalenae (HD = 0.997). These results demonstrate the vagility of the P. magdalenae , in which the strong migratory behavior facilitates the maintenance of high levels of genetic variability, as in species of the genus Prochilodus (Lassala and Renesto, 2007; Santos et al , 2007).…”
Section: Discussioncontrasting
confidence: 60%
“…The present study demonstrates that P. magdalenae has a high genetic diversity, He = 0.877, compared to that observed for other species of the genus (Santacruz, 2003; Hatanaka et al , 2006; Galzerani, 2007; Carvalho-Costa et al , 2008; Silva, 2011; Rueda et al , 2011) and to other commercially important species that have the same reproductive pattern and migrate long distances (Sanches, 2007; Batista, 2010; Dantas, 2010) (Table 4). Likewise, the microsatellite genetic diversity was slightly lower than that reported by Aguirre et al (2013) for mitochondrial DNA (mtDNA control region) in P. magdalenae (HD = 0.997). These results demonstrate the vagility of the P. magdalenae , in which the strong migratory behavior facilitates the maintenance of high levels of genetic variability, as in species of the genus Prochilodus (Lassala and Renesto, 2007; Santos et al , 2007).…”
Section: Discussioncontrasting
confidence: 60%
“…Notably, most of the different mitochondrial haplotypes obtained in this study were singletons (65 %), although present in only one sample. A high number of unique haplotypes and high haplotypic diversity levels are features commonly observed in mtDNA studies of Neotropical migratory fish (Martins et al 2003;Batista and AlvesGomes 2006;Santos et al 2007;Garcez et al 2011;Aguirre-Pabón et al 2013). This pattern seems to be related to the large effective population size maintained in migratory species such as P. lineatus ).…”
Section: Genetic Diversity and Demographic Analysismentioning
confidence: 72%
“…This situation could occur, for example, in the Porto Primavera Reservoir and its tributaries. Some authors have suggested that Prochilodus Agassiz, 1829 characteristics such as large population sizes and high migration capabilities could result in panmictic populations along river basins (Revaldaves et al 1997;Sivasundar et al 2001;Aguirre-Pabón et al 2013). Obviously, the presence of obstacles limiting or preventing gene flow can cause genetic differentiations, such as those obtained for P. lineatus (Garcez et al 2011) and P. costatus (Barroca et al 2012) populations separated by dams in Neotropical River basins.…”
Section: Genetic Structure and Gene Flowmentioning
confidence: 99%
“…To test if the populations of C. hippos follow a pattern of isolation by distance, a correlation analysis among the values of Φst and the geographical distance estimated in Google Earth was performed (Aguirre-Pabón, Narváez Barandica, & Castro García, 2013). The statistical significance was quantified by means of the non-parametric test Mantel after 10 000 permutations in Arlequin Ver 3.0 (Excofer, Smouse, & Quattro, 1992).…”
Section: Genetic Diversity and Genealogical Relationships Of Haplotypesmentioning
confidence: 99%
“…Tajimas' D compares two estimates of mutation parameters (θ) being from a non-coding region that is not exposed to selection. Significant values of D may occur owing to expansion processes, bottlenecks and selection, in conditions where there has been no selective advantage among haplotypes (Rand, 1996;Aguirre-Pabon et al, 2013). The Fu'Fs test compares the number of haplotypes observed with the number of haplotypes expected in a random sample under the assumption of an infinite model without recombination.…”
Section: Demographic History Of the Populationsmentioning
confidence: 99%